2012
DOI: 10.1007/s00726-012-1361-4
|View full text |Cite
|
Sign up to set email alerts
|

Taurine and inflammatory diseases

Abstract: Taurine (2-aminoethanesulfonic acid) is the most abundant free amino acid in humans and plays an important role in several essential biological processes such as bile acid conjugation, maintenance of calcium homeostasis, osmoregulation and membrane stabilization. Moreover, attenuation of apoptosis and its antioxidant activity seem to be crucial for the cytoprotective effects of taurine. Although these properties are not tissue specific, taurine reaches particularly high concentrations in tissues exposed to ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
333
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(369 citation statements)
references
References 97 publications
5
333
0
5
Order By: Relevance
“…It normally exists in tissues and cells in the free form, does not participate in protein synthesis, and is an important endogenous anti-injury substance in the human body [18,19]. Recent studies have shown that Tau is involved in the most important pathway related to tumor metabolism [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It normally exists in tissues and cells in the free form, does not participate in protein synthesis, and is an important endogenous anti-injury substance in the human body [18,19]. Recent studies have shown that Tau is involved in the most important pathway related to tumor metabolism [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of taurine chloramine has also been observed in animal models of collagen-induced arthritis (Marcinkiewicz and Kontny 2013;Kim and Cha 2014). Thus, the studies by Marcinkiewicz and Kontny (2013) support the view that taurine chloramine might at least partially alleviate some symptoms of rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 71%
“…Several of those newly discovered functions have been tied to taurine conjugation. One reaction involves the detoxification of hypochlorous acid by taurine resulting in the formation of taurine chloramine, a product that has the added benefit of possessing anti-inflammatory activity (Schuller-Levis and Park 2003;Marcinkiewicz and Kontny 2013;Kim and Cha 2014). Taurine also forms a conjugate (5-taurinomethyluridine) with the wobble position uridine of tRNA Leu(UUR) , a reaction that enhances the interaction between the modified uridine and guanine (Kirino et al 2005;Kurata et al 2008;Schaffer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations